Pengaruh Kualitas Layanan dan Citra Perusahaan Terhadap Kepuasan Konsumen Serta Dampak pada Loyalitas Konsumen Aplikasi Pijar Sekolah: Studi pada SMK Kartika XIX -1 - Vianty Nadhira; Marheni Eka Saputri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The current development of Information Technology can result in many changes in elements of various fields, one of which is in the world of education. Technological developments in the world of education have experienced many changes in the learning process. With the development of technology through learning platforms, many kinds of increasingly advanced learning methods have emerged, one of which is the emergence of Pijar Sekolah application by PT.Telkom Indonesia, which is a learning media that has very diverse features and of course has been launched with the latest sophistication and formulation, making it easier to develop learning in Indonesia. The purpose of this research is to determine the influence of service quality and company image on customer satisfaction and their impact on school customer loyalty pijar sekolah application at SMK Kartika XIX-1. This research uses quantitative methods with descriptive analysis research type. Sampling was carried out using a probability sampling method, simple random sampling type, with 211 respondents. The data analysis technique uses Partial Least Square Structural Equation Modeling (SEM) with SmartPLS 3 software. Based on the research results, it shows that service quality has a significant effect on customer satisfaction. Company image has a significant effect on customer satisfaction. Service quality has a significant effect on customer loyalty. Company image does not have a significant effect on customer loyalty. Customer satisfaction has a significant effect on customer loyalty. Service quality has a significant effect on customer loyalty through customer satisfaction. Company image has a significant effect on customer loyalty through customer satisfaction.